PPARα: An emerging target of metabolic syndrome, neurodegenerative and cardiovascular diseases - Lin, Yijun; Wang, Yan; Li, Pei-feng (Frontiers in Endocrinology, 2022)
Peroxisome proliferator-activated receptor α (PPARα) is a ligand-activated transcription factor that involves in lipid metabolism of various tissues. Different metabolites of fatty acids and agonists like fibrates activate PPARα for its transactivative or repressive function. PPARα is known to affect diverse human diseases, and we focus on advanced studies of its transcriptional regulation in these diseases. In NAFLD, PPARα shows protective function with its upregulation of lipid oxidation and mitochondrial biogenesis and transcriptional repression of inflammatory genes, which is similar in Alzheimer’s disease and cardiovascular disease. Activation of PPARα also prevents the progress diabetes complications, however, its role in diabetes and cancers remains uncertain. Some PPARα specific agonists, such as Wy14,643 and fenofibrate, has been applied in metabolic syndrome treatment, which might own potential in wider application. Future studies may further explore the functions and interventions of PPARα in cancer, diabetes, immunological diseases and neurodegenerative disease.